2002
DOI: 10.1002/1521-3773(20020517)41:10<1760::aid-anie1760>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Profound Steric Control of Reactivity in Aryl Halide Addition to Bisphosphane Palladium(0) Complexes

Abstract: The steric bulk of the phosphane ligand determines the mechanism of the ArX addition to zero‐valent [PdL2] complexes. This effect has been studied by variation of ligands (catalyst: [Pd(PCxntBu3−n)2]; n=0–3, Cx=cyclohexyl) in Pd couplings of unsaturated electrophiles, and different reaction pathways (A=associative, B=dissociative) identified, depending on the size of the ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 22 publications
8
103
3
Order By: Relevance
“…Since activity in full catalytic studies was significantly decreased under comparable 1:Pd ratios, a decreased level of reactivity was anticipated. The slow oxidative addition of (1) 2 Pd 0 is consistent with the slow rates of oxidative addition of phenyl iodide to (t-Bu 3 P) 2 Pd reported by Jutand [39] and Hartwig [38]. Fu [21] has shown that (t-Bu 3 P) 2 Pd 0 is not a competent Suzuki coupling catalyst unless an equivalent of is Pd 2 (dba) 3 added to encourage monophosphine complex formation.…”
Section: Complexation Studiessupporting
confidence: 82%
“…Since activity in full catalytic studies was significantly decreased under comparable 1:Pd ratios, a decreased level of reactivity was anticipated. The slow oxidative addition of (1) 2 Pd 0 is consistent with the slow rates of oxidative addition of phenyl iodide to (t-Bu 3 P) 2 Pd reported by Jutand [39] and Hartwig [38]. Fu [21] has shown that (t-Bu 3 P) 2 Pd 0 is not a competent Suzuki coupling catalyst unless an equivalent of is Pd 2 (dba) 3 added to encourage monophosphine complex formation.…”
Section: Complexation Studiessupporting
confidence: 82%
“…These gave very encouraging outcomes as the yields and reaction times were greatly improved ( Table 1, entry 2). This finding agrees with the discovery made by Galardon et al [14] that the use of bulky ligands accelerates the elimination step in palladium-catalyzed reactions. We then realized the work of Brett et al [15], describing a procedure that maximizes the efficiency of biaryl dialkylphosphine ligands.…”
Section: Resultssupporting
confidence: 92%
“…Accurate computer calculations of such large complexes need an extremely large computational cost. Additionally, for palladium catalysts based on regular bidentate ligands (e.g., BINAP (I) [31]) and monodentate ligands (e.g., oligo-aryl phosphine (II) and oligo-aryl phosphonites (III) [32]) (Figure 1), several different models of solvation and mono-and biscomplexation should be evaluated [23,[33][34][35][36]. Obviously, a discovery of subtle interactions influencing the absolute configuration of the product formed in the reaction mediated by interconverting complexes of large phosphorus ligands cannot be accurate because of many entropic issues that certainly take place but are difficult to handle.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of C,P-complexes, 12-electron active catalyst is formed by dissociation of the Pd-C coordination bond (Scheme 2), and the energy of this process may influence the reaction rate. Several products of the oxidative addition possessing only one ligand at the phosphorus atom have been obtained and characterised [35,36,50,[60][61][62]. Thus, we decided to shed light on the energetic stability of the model chiral catalytic complex (Scheme 3).…”
Section: Catalyst Activationmentioning
confidence: 99%